2014
DOI: 10.3390/s140202350
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Conductivity and Dielectric Constant of Water–Dioxane Mixtures on the Electrical Response of SiNW-Based FETs

Abstract: In this study, we report on the electrical response of top-down, p-type silicon nanowire field-effect transistors exposed to water and mixtures of water and dioxane. First, the capacitive coupling of the back gate and the liquid gate via an Ag/AgCl electrode were compared in water. It was found that for liquid gating smaller potentials are needed to obtain similar responses of the nanowire compared to back gating. In the case of back gating, the applied potential couples through the buried oxide layer, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…On the contrary, the response of SiO 2 -coated SiNW-FETs to both Na + and K + reported by Park et al was found to be nonlinear . It is noted that in these studies, the electrical conductivity was not kept constant, which affects the response . In our case, however, the electrical conductivity of the two solutions is nearly the same.…”
Section: Results and Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…On the contrary, the response of SiO 2 -coated SiNW-FETs to both Na + and K + reported by Park et al was found to be nonlinear . It is noted that in these studies, the electrical conductivity was not kept constant, which affects the response . In our case, however, the electrical conductivity of the two solutions is nearly the same.…”
Section: Results and Discussioncontrasting
confidence: 71%
“…SiNW-FETs were produced as reported previously. , Briefly, the SiNWs (p-doped at a concentration of 10 16 cm –3 ) are 3 μm in length, 300 nm in width, and 40 nm in height and were covered with a silicon dioxide gate oxide with a thickness of 8 nm. The thickness of the buried oxide (BOX) layer is 300 nm.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the sensing efficacy of our Cu-MOP-modified nanodevice, explosive-containing solutions with different concentrations ranging from the ppb to ppm level were delivered to the sensor chip through a homemade fluid delivery system. 26 To avoid the hydrolysis or desorption of Cu-MOP by water, absolute ethanol was chosen as a solvent. The dependence of the drain−source current (I ds ) on the gate voltage (V g ) at a fixed drain−source voltage (V ds ) for bare, PETES-, and Cu-MOP-modified SiNW devices in the absolute ethanol environment is shown in Figure 2c (see Supporting Information, Section 1.6 for details on the electrical characterization).…”
mentioning
confidence: 64%
“…Before connecting the chip to the semiconductor characterization system, the modified chips were wire-bonded using conductive glue and Al wires (25 μm in diameter) to the chip holder (Figure b, see also Supporting Information, Section 1.5). To assess the sensing efficacy of our Cu-MOP-modified nanodevice, explosive-containing solutions with different concentrations ranging from the ppb to ppm level were delivered to the sensor chip through a homemade fluid delivery system . To avoid the hydrolysis or desorption of Cu-MOP by water, absolute ethanol was chosen as a solvent.…”
mentioning
confidence: 68%
“…Afterwards, a 4-µl suspension (2.5% aqueous suspension) of polystyrene red dyed beads with a diameter of 6 μm and a concentration of 2.10 × 10^8 particles/ml (Warrington, Pennsylvania USA) are diluted in 16-µl of de-ionized water (ε r =80.1; ρ=~20 kΩcm) [29] with a resulting PH of 6.5 and the sample is introduced in the channel inlet.…”
Section: Chip Fabrication and Experimental Setupmentioning
confidence: 99%